2002
DOI: 10.1590/s0066-782x2002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sibutramine on the Treatment of Obesity in Patients with Arterial Hypertension

Abstract: Objective - Effects of Sibutramine on the Treatment of Obesity in Patients with Arterial Hypertension Artigo OriginalThe prevalence of obesity and its associated morbidities has increased in several countries worldwide, including Brazil 1,2 . The increase in body mass index has proved to be a determinant factor for elevation of blood pressure, both for obese and nonobese children and adults 3,4 . In addition, the presence of obesity is related to a 2.5 higher risk of arterial hypertension, mainly in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
1
23
0
5
Order By: Relevance
“…Sibutramine doses -10 mg: six studies [16][17][18]20,22,23 REFERENCES ference in systolic blood pressure was found (the author did not give data on the statistical analyses). However, there was a statistically significant difference favoring the control group, in relation to diastolic blood pressure (CI = 3.51 to 13.29); -Increasing doses, from 5 mg to 20 mg: two studies 19,21 used this scheme and neither of them showed any statistical significance favoring either the experimental or the control group; -Increasing doses, depending on weight loss, up to 20 mg: only one study used this strategy, 9 and it was the only one that found statistical significance for the control group, in relation to both systolic blood and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sibutramine doses -10 mg: six studies [16][17][18]20,22,23 REFERENCES ference in systolic blood pressure was found (the author did not give data on the statistical analyses). However, there was a statistically significant difference favoring the control group, in relation to diastolic blood pressure (CI = 3.51 to 13.29); -Increasing doses, from 5 mg to 20 mg: two studies 19,21 used this scheme and neither of them showed any statistical significance favoring either the experimental or the control group; -Increasing doses, depending on weight loss, up to 20 mg: only one study used this strategy, 9 and it was the only one that found statistical significance for the control group, in relation to both systolic blood and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies 9,[16][17][18][19][20][21][22] presented continuous data that could be analyzed in relation to the outcome of systolic blood pressure (SBP). There were 599 participants in the sibutramine group and 388 in the control group.…”
Section: Systolic Blood Pressure (Sbp)mentioning
confidence: 99%
See 3 more Smart Citations